R&D tax credits and the acquisition of startups - William McShane; Merih Sevilir (Halle Institute for Economic Research (IWH), 2023)
We propose a novel mechanism through which established firms contribute to the startup ecosystem: the allocation of R&D tax credits to startups via the M&A channel. We show that when established firms become eligible for R&D tax credits, they increase their R&D and M&A activity. In particular, they acquire more venture capital (VC)-backed startups, but not non-VC-backed firms. Moreover, the impact of R&D tax credits on firms' R&D is increasing with their acquisition of VC-backed startups. The results suggest that established firms respond to R&D tax credits by acquiring startups rather than solely focusing on increasing their R&D intensity in-house. We also highlight evidence that startups do not appear to benefit from R&D tax credits directly, perhaps because they typically lack the taxable income necessary to directly benefit from the tax credits. In this context, established firms can play an intermediary role by acquiring startups and reallocating R&D tax credits, effectively relaxing the financial constraints faced by startups.
Keywords: G00; G34; H24; M13; O31; 330; indirect effects; innovation; mergers and acquisitions (M&A); research and development (R&D); startups; tax credits